(3cTa GdCSQGQ ddCagGes - (3Ydj Hf eMeO Hf CjOeQ GdLdOcqj , YR GdOjf J (B742 (3g` s; (3GdYQGbj , YHO GdYRjR Hf JeGe GdYQGbj, CHh GdbGSe,J (B762 (3g` s
(3ChdgG (B:s
(3hHYO , aEfg deG cGfJ YGe SfI (B737 (3ef GdgLQI GdfHhjI hQOJ Edi eOjfI OeTb ahLOJ WdGH GdMceI GdEdgjI hGdUfGYI GdMcejI GdadSajI SGJQjf ai XdeGJ YGcajf Ydi eG HCjOjge ef XhGgQ CbhGd GdMceGA s
(3BNQgG (B:s
(3hGdTGQM GdajdSha HeKd GdChd LOjQkG hHdZfG hEjGgeG Lfh hMQjQG s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B244s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B174 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs